Effect of ischemia preconditioning on renal ischemia/reperfusion injury in rats - Lian-hui Fan; Long He; Zhi-qiang Cao; Jun Xiang; Long Liu (International Brazilian Journal of Urology, 2012)
Objective To study the effect of ischemia preconditioning (IP) on renal ischemia/reperfusion (I/R)-associated functional injury and expression of renal adhesion molecules in rats. Materials and Methods The ischemia preconditioning plan adopted in this experiment involved renal warm ischemia for 6 min. and blood flow for 4 min., repeated four times. The Wistar rat kidneys used for warm ischemia preconditioning were subjected to 60 min of renal warm ischemia followed by reperfusion. The rat kidneys with ischemia/reperfusion were compared with the ischemia preconditioning group to observe rat renal function and changes in the expression of renal adhesion molecules ICAM-1, P--Selectin, and E-Selectin. Results The expression of rat renal adhesion molecules (ICAM-1, P-Selectin, and E-Selectin) with ischemia preconditioning was significantly lower than that of the ischemia/reperfusion group. Serum creatinine was significantly lower than that in the ischemia/reperfusion group after 48 hours. Conclusions Ischemia preconditioning has a protective effect on renal function. Reduced expression of renal adhesion molecules is likely a mechanism involved in the observed protection.